Maxwell's Guide to Authority Work. - Maxwell, Robert L. (ALA Editions, 2002)
Authority work is the linchpin of the library catalog. As the author puts it, ''Without authority control, the burden is placed on the user to think of all the possible forms a cataloger might have used to give access in the catalog to a given author or subject.'' If a subject is not sorted by its authorized heading, then the library and its users and staff are left without a system and ultimately the cost of an unsatisfied user. From one of the preeminent experts in the field, this is the step-by-step guide for ensuring that your library and staff are creating and maintaining authority record.